Jack Kennedy [compact disc, unabridged] : elusive hero - Matthews, Chris, 1945- (Simon & Schuster Audio, 2011)
Based on interviews with some of his closest associates, a portrait of the thirty-fifth president discusses his privileged childhood, military service, struggles with a life-threatening disease, and career in politics.